Female obesity and infertility: outcomes and regulatory guidance - Marinelli, Susanna; Napoletano, Gabriele; Straccamore, Marco; Basile, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Obesity has been associated with reduced fertility, although the dynamics and mechanisms which link excess weight to reduced fertility are not yet fully clarified. Obese women, especially those with central obesity, are less likely to conceive per cycle. Obese women suffer from perturbations of the hypothalamus-pituitary-ovary axis, disturbances of the menstrual cycle and are up to three times more likely to suffer from oligo/anovulation. A delicate hormonal balance regulates follicular development and the maturation of oocytes and it has been observed that obesity can alter the hormonal environment: adipocytes, in fact, are responsible for the production of a hormone called leptin (present in high quantities in obese women) which has been associated with reduced fecundity. In addition to compromising ovulation, obesity negatively affects the development and implantation of the endometrium. The expression of polycystic ovary syndrome (PCOS) is regulated, in part, by weight, so obese women with PCOS often have a more severe phenotype and higher subfertility rates. Furthermore, obesity impairs women’s response to medically assisted procreation (MAP) treatments. The authors have set out to delineate a broad-ranging overview of obesity’s impact on female fertility, by drawing upon sources spanning the 1994-2022 period. Assisted reproductive technology (ART) procedures are also discussed as they relate to obese patients. In addition the dynamics by which maternal obesity reportedly affects fetal, neonatal and child development have also been briefly enunciated.